Intravital Microscopy Reveals Endothelial Transcytosis Contributing to Significant Tumor Accumulation of Albumin Nanoparticles - Guoguang Wei; Sihang Zhang; Sheng Yu; Wei Lu (MDPI AG, 2023)
The principle of enhanced permeability and retention (EPR) effect has been used to design anti-cancer nanomedicines over decades. However, it is being challenged due to the poor clinical outcome of nanoparticles and controversial physiological foundation. Herein, we use a near-infrared-II (1000-1700 nm, NIR-II) fluorescence probe BPBBT to investigate the pathway for the entry of human serum albumin-bound nanoparticles (BPBBT-HSA NPs) into tumor compared with BPBBT micelles with phospholipid-poly (ethylene glycol) of the similar particle size about 110 nm. The plasma elimination half-life of BPBBT micelles was 2.8-fold of that of BPBBT-HSA NPs. However, the area under the BPBBT concentration in tumor-time curve to 48 h post-injection (AUCtumor0→48h) of BPBBT-HSA NPs was 7.2-fold of that of BPBBT micelles. The intravital NIR-II fluorescence microscopy revealed that BPBBT-HSA NPs but not BPBBT micelles were transported from the tumor vasculature into tumor parenchyma with high efficiency, and endocytosed by the tumor cells within 3 h post-injection in vivo. This effect was blocked by cross-linking BPBBT-HSA NPs to denature HSA, resulting in the AUCtumor0→48h decreased to 22% of that of BPBBT-HSA NPs. Our results demonstrated that the active process of endothelial transcytosis is the dominant pathway for albumin-bound nanoparticles' entry into tumor.